Determination of baseflow quantity by using unmanned aerial vehicle (UAV) and Google Earth - Tajul Baharuddin, Mohamad Faizal; Awang, Zarizi; Yusoff, Nor Azizi; Embong, Zaidi; Lim, Alvin John Meng Siang (Penerbit UTHM, 2020)
Baseflow is most important in low-flow hydrological features [1]. It is a function of a large number of variables that include factors such as topography, geology, soil, vegetation, and climate. In many catchments, base flow is an important component of streamflow and, therefore, base flow separations have been widely studied and have a long history in science. Baseflow separation methods can be divided into two main groups: non-tracer-based and tracer- based separation methods of hydrology. Besides, the base flow is determined by fitting a unit hydrograph model with information from the recession limbs of the hydrograph and extrapolating it backward.